Quantifying and Mapping the Impact of Construction Land Expansion on Cultivated Land Fragmentation—A Case Study of Fuqing City, China - Xiaoran Yang; Xiping Zheng; Xinyang Yu (Agriculture)
To ensure the sustainable utilization of cultivated land resources, it is essential to quantify and map the characteristics of construction land and cultivated land and analyze the mechanisms by which construction land expansion affects cultivated land. However, few studies have been conducted focusing on this issue. This study integrated morphological spatial pattern analysis, spillover effect analysis, landscape pattern analysis, and a land use transition monitoring method to investigate the characteristics of construction land expansion and cultivated land fragmentation. Fuqing City of China was selected as the case study area for demonstration. The results demonstrated that the expansion of construction land resulted in fragmented patterns within the cultivated land landscape: (1) The large core area of cultivated land was subdivided into smaller core areas during 2000–2020, while the construction land exhibited a tendency towards aggregation and a spillover effect; (2) The expansion rate of the construction land in the study area accelerated, while the extent of the cultivated land decreased; (3) Cultivated land fragmentation intensified as landscape aggregation weakened, leading to an expansion in the agglomeration of construction land. The highlights of this study are: (1) examining the characteristics of construction land expansion and cultivated land fragmentation from morphological and geospatial perspectives; (2) categorizing the core areas of cultivated land based on their size to facilitate the analysis of factors contributing to cultivated land fragmentation. The findings in this study can be used to develop models to predict future patterns of cultivated and construction land to provide suggestions for landscape planning.